Targeting at-risk samples through brief face-to-face interviews in night-time entertainment precincts - Coomber, K.; Chikritzhs, Tanya; Morgan, A.; Lam, Tina; Droste, N.; Mayshak, R.; Curtis, A.; Guadagno, B.; Hyder, S.; Gilmore, William; Peacock, A.; Bruno, R.; et al. (Informa Healthcare, 2017)
© 2017 Taylor & Francis Group, LLC Aims: This exploratory paper investigates the demographic profile of patrons who may be underrepresented in face-to-face interviews by employing a brief version of an interview. Method: Patron interviews (n = 8,664) were conducted in seven Australian cities; 63% completed the full interview and 37% completed the brief interview. Assessed correlates of interview type comprised gender, age, pre-drinking, consumption of alcohol mixed with energy drinks, illicit drug use, involvement in verbal or physical aggression, alcohol-related injuries, and blood alcohol concentration (BAC). Results: Using a brief interview increased the response rate by 34%. Multi-level logistic regression models indicated compared to those who completed the full interview, brief interview respondents were more likely to be: male, have a BAC of =0.05 to < 0.10 or =0.10 g/100 ml, report pre-drinking, and report involvement in physical aggression. Respondents were also less likely to compete the brief interview with each 1 year increase in age. Conclusion: Compared to longer interviews, brief patron interviews can capture a different and more at-risk demographic group and increase the overall response rate. These findings raise questions about the representativeness of long interview samples describing young drinkers who experience aggression. The study also provides the groundwork for future validation of brief interviews.